Study on the use of tobacco among male medical students in Lucknow, India - Kumari Ranjeeta; Nath Bhola (Wolters Kluwer Medknow Publications, 2008)
Objectives: Is use of tobacco a major health problem among medical students? To find out the factors associated with the use of tobacco. Materials and Methods: A cross-sectional study was done on 250 undergraduate male medical students using a pre-designed, pre-tested questionnaire to study about the problem and various correlates of the tobacco use. Data was collected and analysed using Excel and SPSS software. Results: Among the tobacco users (28.8%), smoking was found in 87.5% and tobacco chewing in the form of gutka, khaini, gulmanjan (locally available forms of tobacco) in 37.5% as the predominant means of the use of tobacco. The mean age of our sample was 23.5 years. The residential background, i.e., rural or urban, and religion were not significantly associated with the use of tobacco in the present study. Hostellers were found to be more frequent tobacco users as compared to day-scholars. There was a familial aggregation of the use of tobacco. The factor initiating the use of tobacco was usually peer pressure. Conclusion: Tobacco use is a significant problem among the male medical students and we need to take steps to stop its use by them so as to prevent them from being exposed to its hazardous effects. This will also make their role in the advocacy of the smoking cessation activities more trustworthy.